Impact of Patient Counselling on Knowledge, Attitude and Practice in Management of Diabetes Mellitus among Patients Visiting National Medical College & Teaching Hospital, Birgunj, Nepal - Anil Kumar Shah; Amrullah Shidiki; Sanjay Kumar Sah (Med Phoenix, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) is a major metabolic disease. Counselling of a patient uplifts the patient’s ability to cope with disease and make decisions on its management and medication. The aim of counselling is to provide information about KAP needed for disease management thereby enhancing therapeutic outcomes. Materials and Methods: A case control study was conducted among 113 T2DM patients. The fasting blood sugar (FBS), Post prandial (PP); KAP and medical adherence (MA) scores were obtained with the aid of questionnaires. A control group and intervention group were provided with the questionnaires to assess KAP and MA scores. The intervention group was provided with counselling, information leaflets and medication chart. Data was entered in Microsoft Excel and the statistical methods used were Mann-Whitney U, Wilcoxon’s signed rank and Chi square tests. Results: The mean baseline KAP and MA scores and FBS levels were 11.01 ± 4.29, 8.63 ± 2.51, 6.11 ± 2.42 and 1.98 ± 2.03 and 171.22 ± 50.27 mg/dL, respectively for the intervention group and 12.61 ± 3.18, 8.99 ± 2.19, 6.99 ± 2.28 and 1.64 ± 1.44 and 145.81 ± 50.16 mg/dL for the control group, respectively which improved to 14.56 ± 3.39, 9.58 ± 1.95, 7.98 ± 1.89 and 1.02 ± 1.11 and 131.36 ± 51.28 mg/dL for the intervention group after counselling (p < 0.05). Conclusion: The outcomes of the study emphasize patient counselling provided by the clinicians aid in the improvement of patient’s knowledge about the disease and its management, directly affects the patient’s attitude and practice towards the disease and ultimately helps into better glycemic control.